International Digital Imaging Correlation Society : proceedings of the first Annual Conference, 2016 - Sutton, Michael Albert, 1950-; Reu, Phillip L. (Springer, 2017)
This collection represents a single volume of technical papers presented at the Annual International DIC Society Conference and SEM Fall Conference organized by the Society for Experimental Mechanics and Sandia National Laboratories and held in Philadelphia, PA, November 7-10, 2016. The volume presents early findings from experimental, standards development and various other investigations concerning digital image correlation - an important area within Experimental Mechanics. The area of Digital Image Correlation has been an integral track within the SEM Annual Conference spearheaded by Professor Michael Sutton from the University of South Carolina. In 2016, the SEM and Sandia joined their collaborative strengths to launch a standing fall meeting focusing specifically on developments in the area of Digital Image Correlation. The contributed papers within this volume span numerous technical aspects of DIC including standards development for the industry.
Keywords: Digital image correlation -- Congresses.; Image processing -- Digital techniques -- Congresses.; elektronické knihy; electronic books